The bears on Hemlock Mountain - Dalgliesh, Alice 1893-; Sewell, Helen 1896-. (New York Scribner, 1952)
A young boy sent on an errand over Hemlock Mountain is not so sure he likes going alone, because there may be bears on the mountain, but with the help of the big iron pot he borrows, he completes his errand.
Keywords: Bears -- Fiction; Bears -- Stories